The effect of some Diels-Alder adducts of resin acids on the process of epoxy resin curing - Mustata, F.; Bicu, I. (Polimery, 2022)
Curing reaction of epoxy resins with three Diels-Alder adducts of resin acids in the presence of triethylbenzylammonium chloride as catalyst was examined by differential scanning calorimetry at different heating rates. Using the literature methods (Kissinger and Ozawa) the kinetic parameters of crosslinking reactions were obtained. The activation energies of the curing reactions varied in the range of 44-79kJźmol-1 depending on epoxy systems and curing agents. The thermal behavior of cured products was also investigated using thermogravimetric analysis. The cured products present good thermal stability - the activation energies of the degradation process have values between 87 to 165kJźmol-1.